Hair Cortisol and Salivary Cortisol Reactivity in Adolescents - Salvatore, John J. (Tufts Archival Research Center, 2005)
The HPA axis is initiated in response to stress, resulting in a hormonal cascade that culminates in the release of glucocorticoids. Glucocorticoids mediate many physiological changes in response to environmental challenges. Ultimately, they provide negative feedback to the brain regions that activate the HPA axis. When secreted chronically, however, glucocorticoids can damage neurons that regulate the axis. This possibility may be magnified during developmental critical periods, when the brain is most sensitive to environmental influences. Studies in animals suggest adolescents may be particularly vulnerable to the deleterious effects chronic stress. The present study hypothesized that adolescents exposed to chronic activation of the HPA axis would exhibit heightened reactivity to the Trier Social Stress Task (TSST). The accumulation of cortisol in hair was used as a biomarker of chronic activation of the HPA axis in order to investigate its relationship with subjective reports of stress and its impact on subsequent reactivity. Surprisingly, adolescent reports of high perceived stress significantly predicted decreased hair cortisol content.